Long-term high loading intensity of aerobic exercise improves skeletal muscle performance via the gut microbiota-testosterone axis - Zhang, Lidong; Lang, Hedong; Ran, Li; Tian, Guoliang; Shen, Hui; Zhu, Jundong; Zhang, Qianyong; Yi, Long; Mi, Mantian (Frontiers in Microbiology, 2022)
Exercise is reported to play a crucial role in skeletal muscle performance. However, the underlying mechanism is still unknown. Thus, we investigated the effect of high-intensity aerobic exercise on skeletal muscle performance. In this study, the male C57BL/6J mice were accepted by high-intensity aerobic exercise for 8 weeks to establish an exercise model. It was observed that high-intensity aerobic exercise markedly affected the expression of genes in skeletal muscle. Moreover, high-intensity aerobic exercise significantly improved skeletal muscle grip strength and serum testosterone levels. HE staining showed that the cross-sectional area (CSA) of the skeletal muscle was successfully increased after 8 weeks of high-intensity aerobic exercise. Additionally, we found that high-intensity aerobic exercise changed gut microbiota structure by altering the abundance of Akkermansia, Allobaculum, and Lactobacillus, which might be related to testosterone production. However, the beneficial effects disappeared after the elimination of the gut microbiota and recovered after fecal microbiota transplantation (FMT) experiments for 1 week. These results indicated that the beneficial effects of high-intensity aerobic exercise on skeletal muscle were partly dependent on the gut microbiota. Our results suggested that long-term high loading intensity of aerobic exercise could improve skeletal muscle performance, which was probably due to the gut microbiota-testosterone axis.